Preparation method of bonded magnet with low magnetic energy product and high coercive force

Through the dry-wet-dry combination method, the strontium ferrite magnetic powder and neodymium iron boron magnetic powder are uniformly mixed, which solves the problems of poor magnetic performance consistency and insufficient corrosion resistance caused by uneven mixing in the prior art, and achieves high coercive force and the continuously adjustable magnetic energy product improve the cost-effectiveness of the product.

CN119230275AActive Publication Date: 2024-12-31HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411248185.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-31
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

In the prior art, the mixed mixing of ferrite neodymium iron boron during the production process of ferrite, due to differences in magnetic powder performance, resulting in poor magnetic consistency, large product magnetic reduction rate, unstable pressing, low magnet strength, and insufficient corrosion resistance. .

Method used

Using the method of dry and wet combination, the strontium ferrite magnetic powder is uniformly mixed with the neodymium iron boron magnetic powder. By controlling the stirring speed and temperature, the glue liquid is used to make the magnetic powder evenly contact and adhere to the magnetic powder. After combining crushing and sieving, it is carried out. Molding ensures uniform composite and filling characteristics of the magnetic powder.

Benefits of technology

It realizes continuous adjustable magnetic energy product, and the coercive force reaches more than 7KOe, which improves the cost-effectiveness of the product, ensures consistency of magnetic performance and corrosion resistance, and solves the problems of changes in magnet strength and crush strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005031474160000131
    Figure BDA0005031474160000131
Patent Text Reader

Abstract

The invention discloses a preparation method of a bonded magnet with low magnetic energy product and high coercive force. The preparation method comprises the following steps: dissolving magnetic powder into an organic solvent to obtain a glue solution; adding the glue solution into the strontium ferrite magnetic powder, and heating and stirring at the rotating speed of 15-30r / min; adding neodymium iron boron magnetic powder, continuously stirring, adjusting the rotating speed to 10-20 r / min, and vacuumizing until the vacuum degree is 0.08-0.1 Pa; stopping vacuumizing, adjusting the rotating speed to 50-60r / min, cooling to 5 + / -5 DEG C, and continuously stirring to obtain mixed magnetic powder; the mixed magnetic powder is crushed and screened and then subjected to compression molding; and sequentially carrying out heating curing, epoxy resin surface treatment and magnetizing on the molded product. According to the method, dry-method mixing and wet-method mixing are effectively combined, the evenly-mixed magnetic powder is obtained, the finished magnet meets the requirement, the magnetic energy product is continuously adjustable while high coercive force is kept, and the cost performance of the magnetic powder is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bonded NdFeB magnet preparation, in particular to a method for preparing a bonded magnet with low magnetic energy product and high coercive force. Background Art

[0002] The traditional process steps of bonded NdFeB magnet compression molding are: mixing-pressing-curing-surface treatment-magnetization; the relevant process technologies are developed and improved based on the use of 100% rapid quenching NdFeB magnetic powder. With the expansion of the application field of bonded magnets, more requirements are put forward for the performance of magnets, and magnets made of 100% NdFeB magnetic powder begin to fail to meet the requirements. On this basis, composite magnetic powder has been widely studied and applied.

[0003] In the application of ferrite and NdFeB composite magnetic powder, the performance of NdFeB magnetic powder is much higher than that of strontium ferrite magnetic powder. The magnetic energy product (BH) max of bonded NdFeB magnetic powder is 6-12MGOe, while the maximum magnetic energy product (BH) max of sintered ferrite is 4.5MGOe. However, the price of NdFeB magnetic powder is 100,000-300,000 yuan / ton, and the price of ferrite magnet is 3,000-7,000 yuan / ton. The high price of raw materials has greatly limited the promotion and application of bonded NdFeB. By replacing raw materials, while ensuring that the magnetic properties meet the requirements, reducing material costs and improving cost performance have become an important way to promote the application of bonded NdFeB. The alternative materials include copper powder, zinc powder, ferrite powder, etc. The most widespread application is to partially replace NdFeB with ferrite. For example, patent CN117690682A discloses a ferrite-NdFeB hybrid magnet and a preparation method thereof, which combines ferrite magnetic powder and NdFeB magnetic powder to improve the comprehensive magnetic properties of the magnet while reducing the manufacturing cost.

[0004] However, the existing technology generally adopts the method of ball milling mixing + spray granulation to pre-treat the composite magnetic powder. Due to the different characteristics of ferrite magnetic powder and NdFeB magnetic powder, it is difficult to mix them evenly. The ferrite powder is spherical, with an average particle size of 0.8-6μm and a density of about 4.0g / cm 3 ; NdFeB powder is flaky, with an average particle size of 20-35μm and a density of about 7.0g / cm 3Compared with NdFeB magnetic powder, ferrite magnetic powder is light and fine, which makes it difficult to mix evenly, the stratification is very obvious, and the consistency of magnetic properties is difficult to ensure. This will lead to large differences in magnetic properties of different products and large product demagnetization rates. In addition, after the composite magnetic powder is mixed unevenly, the filling characteristics of the magnetic powder in different parts of the same batch of magnetic powder vary greatly, which is mainly reflected in the fluidity and loose packing ratio of the powder. In the same mold cavity, sometimes the filling is fast and sometimes it is slow, which will lead to unstable pressing, continuous pressing is not smooth, and the mold is often stuck and over-pressure. After mixing evenly, it also affects the local magnet strength. If the local magnetic powder particles are fine and there is not much magnetic powder glue, the magnet strength will be low, the corners will be damaged, and the product's crushing strength will vary greatly. In addition, strontium ferrite magnetic powder is an oxide, and neodymium iron boron magnetic powder is an alloy. The surface energy difference is large, and the mixing is uneven, which will lead to different local film thickness after electrophoresis coating of epoxy resin paint, resulting in rust of the product under salt spray test, and the corrosion resistance cannot be guaranteed. Summary of the invention

[0005] The present invention aims to overcome the above-mentioned problems existing in the production process of ferrite NdFeB hybrid magnets in the prior art, and provides a method for preparing a bonded magnet with low magnetic energy product and high coercive force. By effectively combining dry and wet mixing methods, uniformly mixed magnetic powder is obtained, and the finished magnet meets the requirements, achieving continuous adjustment of the magnetic energy product while maintaining high coercive force, thereby greatly improving the cost-effectiveness of the magnetic powder.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a bonded magnet with low magnetic energy product and high coercivity, comprising: (1) dissolving magnetic powder glue in an organic solvent to obtain glue solution; (2) Add the glue solution to the strontium ferrite magnetic powder and stir at a speed of 15 to 30 r / min for 10 to 20 minutes at 40±5°C; (3) Adding NdFeB magnetic powder, stirring for 15 to 25 minutes under the same conditions, adjusting the speed to 10 to 20 r / min, and evacuating to a vacuum degree of 0.08 to 0.1 Pa; stopping evacuating, adjusting the speed to 50 to 60 r / min, cooling to 5±5°C, and continuing stirring for 5 to 15 minutes to obtain mixed magnetic powder; the strontium ferrite magnetic powder added is 0 to 70% of the mass of the NdFeB magnetic powder; (4) crushing and screening the mixed magnetic powder and then performing compression molding; (5) The molded product is heated and cured, subjected to epoxy resin surface treatment and magnetized in sequence.

[0007] The present invention mixes strontium ferrite magnetic powder and neodymium iron boron magnetic powder by a dry-wet combination method. When the magnetic powder is mixed, the strontium ferrite magnetic powder and the glue are first stirred and mixed, and the stirring speed is controlled appropriately to allow the glue to slowly penetrate, so that the magnetic powder glue can be in uniform contact with the magnetic powder; when the stirring speed is too slow, the magnetic powder flows too slowly, the glue is difficult to penetrate evenly, and the magnetic powder glue and the magnetic powder cannot be mixed evenly; and when the speed is too fast, it is easy to cause local magnetic powder agglomeration, which also causes the magnetic powder and the magnetic powder glue to be mixed unevenly. At the same time, during the stirring process, the present invention also heats to allow the organic solvent in the glue to evaporate slowly, and by controlling the heating temperature and stirring time, the volatilization amount of the organic solvent is controlled, so that the humidity of the magnetic powder glue on the surface of the strontium ferrite magnetic powder is maintained in a suitable state. If the organic solvent is not fully volatilized, the magnetic powder glue is always in liquid state and cannot be adsorbed on the surface of the magnetic powder and solidified; but if the organic solvent evaporates too much, the magnetic powder glue has been fully solidified on the surface of the magnetic powder, and the neodymium iron boron magnetic powder can no longer be adsorbed subsequently.

[0008] After the strontium ferrite magnetic powder and the glue are evenly mixed, and the dryness and humidity of the magnetic powder glue on its surface are adjusted to a suitable state, add the dry NdFeB magnetic powder and stir and mix them at the same temperature and speed first; because the NdFeB magnetic powder is mostly flaky and several times larger than the strontium ferrite magnetic powder, the dry NdFeB magnetic powder flows quickly under the action of stirring, and the semi-wet and semi-dry strontium ferrite powder can be evenly adhered to the surface of the dry NdFeB magnetic powder, so that the two are evenly compounded; the stirring speed in this process cannot be too slow, otherwise the magnetic powder will not flow, which is not conducive to the uniform adhesion of the strontium ferrite magnetic powder on the surface of the NdFeB magnetic powder; at the same time, the stirring speed cannot be too fast, otherwise the strontium ferrite magnetic powder with the magnetic powder glue adsorbed on the surface will self-agglomerate and form large lumps. After the strontium ferrite magnetic powder is evenly adhered to the surface of the neodymium iron boron magnetic powder, the speed is lowered and vacuuming is started. Under the action of vacuuming, the non-volatile organic solvent in the glue liquid can be completely volatilized and the magnetic powder glue is solidified; then the vacuuming is stopped, cooling is started, and the speed is increased to continue stirring. At low temperature, the magnetic powder can be further broken up, and finally a mixed magnetic powder of strontium ferrite magnetic powder and neodymium iron boron magnetic powder evenly compounded is obtained.

[0009] The present invention adjusts the dosage ratio of strontium ferrite magnetic powder and neodymium iron boron magnetic powder, while maintaining high coercive force, can achieve continuous adjustment of magnetic energy product, meet the requirements of magnetic properties in different fields, and improve product cost performance. If the addition ratio of strontium ferrite magnetic powder is too small, the adjustable range of magnetic powder performance is narrow, and it is not conducive to reducing costs; and if too much strontium ferrite magnetic powder is added, it cannot be evenly adhered to the surface of neodymium iron boron magnetic powder, and uniform mixing cannot be achieved. The present invention effectively combines dry and wet mixing to achieve uniform mixing of strontium ferrite magnetic powder and neodymium iron boron magnetic powder. The magnetic properties of the bonded magnet obtained are consistent, and continuous pressing is smooth during compression molding, and it is not easy to get stuck. The crushing strength of the magnet does not change much, and it is not easy to have problems such as corner defects; at the same time, the uniform mixing of the two magnetic powders can also ensure uniform adsorption of epoxy resin on the surface, and the magnet has good corrosion resistance and is not easy to rust under salt spray test.

[0010] Preferably, the average particle size of the strontium ferrite magnetic powder is 400-600 meshes, and the average particle size of the neodymium iron boron magnetic powder is 100-250 meshes.

[0011] Preferably, the components of the magnetic powder adhesive in step (1) include, by weight: 2 to 3 parts of epoxy resin, 0.35 to 0.55 parts of curing agent, and 0.02 to 0.04 parts of coupling agent.

[0012] Preferably, the curing agent is dicyandiamide and the coupling agent is KH550.

[0013] Preferably, the mass of the magnetic powder glue in the glue solution is 1.5-3.0% of the total mass of the strontium ferrite magnetic powder and the neodymium iron boron magnetic powder, and the mass of the organic solvent is 5-10% of the total mass of the strontium ferrite magnetic powder and the neodymium iron boron magnetic powder. If too little magnetic powder glue is added, the strength of the product cannot meet the requirements; if too much magnetic powder glue is added, not only will the magnetic properties per unit volume decrease, but it will also easily overflow, resulting in poor appearance. Too little organic solvent will cause part of the strontium ferrite magnetic powder to not be fully infiltrated by the organic solvent, the surface magnetic powder glue is less, the magnetic powder is unevenly mixed, and the product strength is low; too much organic solvent will make it difficult for the organic solvent to fully volatilize, affecting the mixing effect.

[0014] Preferably, in step (4), the mixed magnetic powder is vibrated and crushed by a Φ10×10 stainless steel ball, and sieved through a 40-80 mesh sieve.

[0015] Preferably, the pressure during compression molding in step (4) is 8-10T / cm 2 .

[0016] Preferably, the temperature during heating and curing in step (5) is 180±10°C, and the curing time is 50±10min.

[0017] Preferably, the thickness of the surface epoxy resin layer in step (5) is 0.015 to 0.025 mm.

[0018] Therefore, the present invention has the following beneficial effects: (1) Achieve continuous adjustment of the magnetic energy product between 3.0 and 8.0 MGOe, and achieve a coercive force of more than 7 KOe, meeting the requirements of magnetic properties in different fields and improving product cost performance; (2) The mixing is carried out by combining dry and wet methods, which solves the problem of poor magnetic property consistency caused by the difficulty in mixing evenly when strontium ferrite magnetic powder partially replaces neodymium iron boron magnetic powder due to the difference in magnetic powder properties; (3) The problems of poor magnet strength, easy chipping and mold sticking during compression molding of strontium ferrite and neodymium iron boron composite magnetic powders are solved; (4) The problem of easy rust of magnets made of strontium ferrite and neodymium iron boron composite magnetic powders after being covered with epoxy resin paint is solved. DETAILED DESCRIPTION

[0019] The present invention is further described below in conjunction with specific implementation methods.

[0020] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.

[0021] Overall embodiment: A method for preparing a bonded magnet with low magnetic energy product and high coercivity, comprising: (1) dissolving magnetic powder glue in an organic solvent to obtain glue solution; (2) Add the glue solution to the strontium ferrite magnetic powder and stir at a speed of 15 to 30 r / min for 10 to 20 minutes at 40±5°C; (3) Adding NdFeB magnetic powder, stirring for 15 to 25 minutes under the same conditions, adjusting the speed to 10 to 20 r / min, and evacuating to a vacuum degree of 0.08 to 0.1 Pa; stopping evacuating, adjusting the speed to 50 to 60 r / min, cooling to 5±5°C, and continuing stirring for 5 to 15 minutes to obtain mixed magnetic powder; the strontium ferrite magnetic powder added is 0 to 70% of the mass of the NdFeB magnetic powder; (4) crushing and screening the mixed magnetic powder and then performing compression molding; (5) The molded product is heated and cured, subjected to epoxy resin surface treatment and magnetized in sequence.

[0022] As a specific implementation, the average particle size of the strontium ferrite magnetic powder is 400-600 meshes, and the average particle size of the neodymium iron boron magnetic powder is 100-250 meshes.

[0023] As a specific implementation, the components of the magnetic powder adhesive in step (1) include, by weight: 2 to 3 parts of epoxy resin, 0.35 to 0.55 parts of curing agent, and 0.02 to 0.04 parts of coupling agent.

[0024] As a specific implementation, the curing agent is dicyandiamide and the coupling agent is KH550.

[0025] As a specific implementation, the mass of the magnetic powder glue added to the glue solution is 1.5-3.0% of the total mass of the strontium ferrite magnetic powder and the neodymium iron boron magnetic powder, and the mass of the organic solvent is 5-10% of the total mass of the strontium ferrite magnetic powder and the neodymium iron boron magnetic powder.

[0026] As a specific implementation method, in step (4), the mixed magnetic powder is vibrated and crushed by a Φ10×10 stainless steel ball, and then sieved through a 40-80 mesh sieve.

[0027] As a specific embodiment, the pressure during the compression molding in step (4) is 8-10T / cm 2 .

[0028] As a specific implementation, the temperature during heating and curing in step (5) is 180±10° C., and the curing time is 50±10 min.

[0029] As a specific implementation, the thickness of the surface epoxy resin layer in step (5) is 0.015 to 0.025 mm.

[0030] Embodiment 1: A method for preparing a bonded magnet with low magnetic energy product and high coercivity, comprising the following steps: (1) By weight, 2.5 parts of epoxy resin W-6C, 0.03 parts of curing agent dicyandiamide, and 0.03 parts of silane coupling agent KH550 were mixed uniformly to obtain magnetic powder adhesive; (2) adding magnetic powder glue into acetone, stirring and dissolving it evenly with a stirrer to obtain glue solution; (3) Weigh strontium ferrite magnetic powder (average particle size 500 mesh) and add it to the mixer, then add the glue solution and start stirring at a speed of 20 r / min; while stirring, heat the temperature in the container to 40°C and stir for 15 minutes; (4) Add NdFeB magnetic powder (grade 8-11, average particle size 200 mesh) into the mixer, and continue stirring at a speed of 20 r / min for 20 min; adjust the speed to 15 r / min and continue stirring, and evacuate to a vacuum degree of 0.09 Pa; stop evacuating, adjust the speed to 55 r / min, cool to 5°C with cooling water, and continue stirring for 10 min to obtain mixed magnetic powder; the added strontium ferrite magnetic powder is 5% of the mass of the NdFeB magnetic powder, the mass of the magnetic powder glue in the glue solution is 2.0% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder, and the mass of the organic solvent is 8% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder; (5) The mixed magnetic powder is crushed by a Φ10×10 stainless steel ball and passed through a 60-mesh sieve; (6) at 10T / cm 2 Under the pressing pressure of , the screened mixed magnetic powder is pressed into a ring of Φ15×Φ9.8×8.45mm through a mold; (7) The molded product is heated and cured at 180°C for 50 minutes; (8) The cured product is surface treated with electrophoretic epoxy resin (EP-703) at a film thickness of 0.020 mm; (9) Magnetizing the surface treated product to obtain the bonded magnet with low magnetic energy product and high coercive force.

[0031] Embodiment 2: A method for preparing a bonded magnet with low magnetic energy product and high coercivity, comprising the following steps: (1) By weight, 2.5 parts of epoxy resin W-6C, 0.03 parts of curing agent dicyandiamide, and 0.03 parts of silane coupling agent KH550 were mixed uniformly to obtain magnetic powder adhesive; (2) adding magnetic powder glue into acetone, stirring and dissolving it evenly with a stirrer to obtain glue solution; (3) Weigh strontium ferrite magnetic powder (average particle size 500 mesh) and add it to the mixer, then add the glue solution and start stirring at a speed of 15 r / min; while stirring, heat the temperature in the container to 35°C and stir for 20 minutes; (4) Add NdFeB magnetic powder (grade 8-11, average particle size 200 mesh) into the mixer and continue stirring at a speed of 15 r / min for 25 min; adjust the speed to 10 r / min and continue stirring, and evacuate to a vacuum degree of 0.08 Pa; stop evacuating, adjust the speed to 50 r / min, cool to 5° C. with cooling water, and continue stirring for 15 min to obtain mixed magnetic powder; the strontium ferrite magnetic powder added is 5% of the mass of the NdFeB magnetic powder, the mass of the magnetic powder glue in the glue solution is 2.0% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder, and the mass of the organic solvent is 8% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder; (5) The mixed magnetic powder is crushed by a Φ10×10 stainless steel ball and passed through a 60-mesh sieve; (6) at 10T / cm 2 Under the pressing pressure of , the screened mixed magnetic powder is pressed into a ring of Φ15×Φ9.8×8.45mm through a mold; (7) The molded product is heated and cured at 180°C for 50 minutes; (8) The cured product is surface treated with electrophoretic epoxy resin (EP-703) at a film thickness of 0.020 mm; (9) Magnetizing the surface treated product to obtain the bonded magnet with low magnetic energy product and high coercive force.

[0032] Embodiment 3: A method for preparing a bonded magnet with low magnetic energy product and high coercivity, comprising the following steps: (1) By weight, 2.5 parts of epoxy resin W-6C, 0.03 parts of curing agent dicyandiamide, and 0.03 parts of silane coupling agent KH550 were mixed uniformly to obtain magnetic powder adhesive; (2) adding magnetic powder glue into acetone, stirring and dissolving it evenly with a stirrer to obtain glue solution; (3) Weigh strontium ferrite magnetic powder (average particle size 500 mesh) and add it to the mixer, then add the glue solution and start stirring at a speed of 30 r / min; while stirring, heat the temperature in the container to 45°C and stir for 10 minutes; (4) Add NdFeB magnetic powder (grade 8-11, average particle size 200 mesh) into the mixer, and continue stirring at a speed of 30 r / min for 15 min; adjust the speed to 20 r / min and continue stirring, and evacuate to a vacuum degree of 0.1 Pa; stop evacuating, adjust the speed to 60 r / min, cool to 5°C with cooling water, and continue stirring for 5 min to obtain mixed magnetic powder; the added strontium ferrite magnetic powder is 5% of the mass of the NdFeB magnetic powder, the mass of the magnetic powder glue in the glue solution is 2.0% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder, and the mass of the organic solvent is 8% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder; (5) The mixed magnetic powder is crushed by a Φ10×10 stainless steel ball and passed through a 60-mesh sieve; (6) at 10T / cm 2 Under the pressing pressure of , the screened mixed magnetic powder is pressed into a ring of Φ15×Φ9.8×8.45mm through a mold; (7) The molded product is heated and cured at 180°C for 50 minutes; (8) The cured product is surface treated with electrophoretic epoxy resin (EP-703) at a film thickness of 0.020 mm; (9) Magnetizing the surface treated product to obtain the bonded magnet with low magnetic energy product and high coercive force.

[0033] Embodiment 4: A method for preparing a bonded magnet with low magnetic energy product and high coercivity, comprising the following steps: (1) By weight, 2.5 parts of epoxy resin W-6C, 0.03 parts of curing agent dicyandiamide, and 0.03 parts of silane coupling agent KH550 were mixed uniformly to obtain magnetic powder adhesive; (2) adding magnetic powder glue into acetone, stirring and dissolving it evenly with a stirrer to obtain glue solution; (3) Weigh strontium ferrite magnetic powder (average particle size 500 mesh) and add it to the mixer, then add the glue solution and start stirring at a speed of 20 r / min; while stirring, heat the temperature in the container to 40°C and stir for 15 minutes; (4) Add NdFeB magnetic powder (grade 8-11, average particle size 200 mesh) into the mixer and continue stirring at a speed of 20 r / min for 20 min; adjust the speed to 15 r / min and continue stirring, and evacuate to a vacuum degree of 0.09 Pa; stop evacuating, adjust the speed to 55 r / min, cool to 5°C with cooling water, and continue stirring for 10 min to obtain mixed magnetic powder; the added strontium ferrite magnetic powder is 10% of the mass of the NdFeB magnetic powder, the mass of the magnetic powder glue in the glue solution is 2.0% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder, and the mass of the organic solvent is 8% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder; (5) The mixed magnetic powder is crushed by a Φ10×10 stainless steel ball and passed through a 60-mesh sieve; (6) at 10T / cm 2 Under the pressing pressure of , the screened mixed magnetic powder is pressed into a ring of Φ15×Φ9.8×8.45mm through a mold; (7) The molded product is heated and cured at 180°C for 50 minutes; (8) The cured product is surface treated with electrophoretic epoxy resin (EP-703) at a film thickness of 0.020 mm; (9) Magnetizing the surface treated product to obtain the bonded magnet with low magnetic energy product and high coercive force.

[0034] Embodiment 5: A method for preparing a bonded magnet with low magnetic energy product and high coercivity, comprising the following steps: (1) By weight, 2.5 parts of epoxy resin W-6C, 0.03 parts of curing agent dicyandiamide, and 0.03 parts of silane coupling agent KH550 were mixed uniformly to obtain magnetic powder adhesive; (2) adding magnetic powder glue into acetone, stirring and dissolving it evenly with a stirrer to obtain glue solution; (3) Weigh strontium ferrite magnetic powder (average particle size 500 mesh) and add it to the mixer, then add the glue solution and start stirring at a speed of 20 r / min; while stirring, heat the temperature in the container to 40°C and stir for 15 minutes; (4) Add NdFeB magnetic powder (grade 8-11, average particle size 200 mesh) into the mixer and continue stirring at a speed of 20 r / min for 20 min; adjust the speed to 15 r / min and continue stirring, and evacuate to a vacuum degree of 0.09 Pa; stop evacuating, adjust the speed to 55 r / min, cool to 5°C with cooling water, and continue stirring for 10 min to obtain mixed magnetic powder; the added strontium ferrite magnetic powder is 20% of the mass of the NdFeB magnetic powder, the mass of the magnetic powder glue in the glue solution is 2.0% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder, and the mass of the organic solvent is 8% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder; (5) The mixed magnetic powder is crushed by a Φ10×10 stainless steel ball and passed through a 60-mesh sieve; (6) at 10T / cm 2 Under the pressing pressure of , the screened mixed magnetic powder is pressed into a ring of Φ15×Φ9.8×8.45mm through a mold; (7) The molded product is heated and cured at 180°C for 50 minutes; (8) The cured product is surface treated with electrophoretic epoxy resin (EP-703) at a film thickness of 0.020 mm; (9) Magnetizing the surface treated product to obtain the bonded magnet with low magnetic energy product and high coercive force.

[0035] Embodiment 6: A method for preparing a bonded magnet with low magnetic energy product and high coercivity, comprising the following steps: (1) By weight, 2.5 parts of epoxy resin W-6C, 0.03 parts of curing agent dicyandiamide, and 0.03 parts of silane coupling agent KH550 were mixed uniformly to obtain magnetic powder adhesive; (2) adding magnetic powder glue into acetone, stirring and dissolving it evenly with a stirrer to obtain glue solution; (3) Weigh strontium ferrite magnetic powder (average particle size 500 mesh) and add it to the mixer, then add the glue solution and start stirring at a speed of 20 r / min; while stirring, heat the temperature in the container to 40°C and stir for 15 minutes; (4) Add NdFeB magnetic powder (grade 8-11, average particle size 200 mesh) into the mixer and continue stirring at a speed of 20 r / min for 20 min; adjust the speed to 15 r / min and continue stirring, and evacuate to a vacuum degree of 0.09 Pa; stop evacuating, adjust the speed to 55 r / min, cool to 5°C with cooling water, and continue stirring for 10 min to obtain mixed magnetic powder; the added strontium ferrite magnetic powder is 30% of the mass of the NdFeB magnetic powder, the mass of the magnetic powder glue in the glue solution is 2.0% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder, and the mass of the organic solvent is 8% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder; (5) The mixed magnetic powder is crushed by a Φ10×10 stainless steel ball and passed through a 60-mesh sieve; (6) at 10T / cm 2 Under the pressing pressure of , the screened mixed magnetic powder is pressed into a ring of Φ15×Φ9.8×8.45mm through a mold; (7) The molded product is heated and cured at 180°C for 50 minutes; (8) The cured product is surface treated with electrophoretic epoxy resin (EP-703) at a film thickness of 0.020 mm; (9) Magnetizing the surface treated product to obtain the bonded magnet with low magnetic energy product and high coercive force.

[0036] Embodiment 7: A method for preparing a bonded magnet with low magnetic energy product and high coercivity, comprising the following steps: (1) By weight, 2.5 parts of epoxy resin W-6C, 0.03 parts of curing agent dicyandiamide, and 0.03 parts of silane coupling agent KH550 were mixed uniformly to obtain magnetic powder adhesive; (2) adding magnetic powder glue into acetone, stirring and dissolving it evenly with a stirrer to obtain glue solution; (3) Weigh strontium ferrite magnetic powder (average particle size 500 mesh) and add it to the mixer, then add the glue solution and start stirring at a speed of 20 r / min; while stirring, heat the temperature in the container to 40°C and stir for 15 minutes; (4) Add NdFeB magnetic powder (grade 8-11, average particle size 200 mesh) into the mixer and continue stirring at a speed of 20 r / min for 20 min; adjust the speed to 15 r / min and continue stirring, and evacuate to a vacuum degree of 0.09 Pa; stop evacuating, adjust the speed to 55 r / min, cool to 5°C with cooling water, and continue stirring for 10 min to obtain mixed magnetic powder; the added strontium ferrite magnetic powder is 50% of the mass of the NdFeB magnetic powder, the mass of the magnetic powder glue in the glue solution is 2.0% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder, and the mass of the organic solvent is 8% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder; (5) The mixed magnetic powder is crushed by a Φ10×10 stainless steel ball and passed through a 60-mesh sieve; (6) at 10T / cm 2 Under the pressing pressure of , the screened mixed magnetic powder is pressed into a ring of Φ15×Φ9.8×8.45mm through a mold; (7) The molded product is heated and cured at 180°C for 50 minutes; (8) The cured product is surface treated with electrophoretic epoxy resin (EP-703) at a film thickness of 0.020 mm; (9) Magnetizing the surface treated product to obtain the bonded magnet with low magnetic energy product and high coercive force.

[0037] Embodiment 8: A method for preparing a bonded magnet with low magnetic energy product and high coercivity, comprising the following steps: (1) By weight, 2.5 parts of epoxy resin W-6C, 0.03 parts of curing agent dicyandiamide, and 0.03 parts of silane coupling agent KH550 were mixed uniformly to obtain magnetic powder adhesive; (2) adding magnetic powder glue into acetone, stirring and dissolving it evenly with a stirrer to obtain glue solution; (3) Weigh strontium ferrite magnetic powder (average particle size 500 mesh) and add it to the mixer, then add the glue solution and start stirring at a speed of 20 r / min; while stirring, heat the temperature in the container to 40°C and stir for 15 minutes; (4) Add NdFeB magnetic powder (grade 8-11, average particle size 200 mesh) into the mixer and continue stirring at a speed of 20 r / min for 20 min; adjust the speed to 15 r / min and continue stirring, and evacuate to a vacuum degree of 0.09 Pa; stop evacuating, adjust the speed to 55 r / min, cool to 5°C with cooling water, and continue stirring for 10 min to obtain mixed magnetic powder; the added strontium ferrite magnetic powder is 70% of the mass of the NdFeB magnetic powder, the mass of the magnetic powder glue in the glue solution is 2.0% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder, and the mass of the organic solvent is 8% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder; (5) The mixed magnetic powder is crushed by a Φ10×10 stainless steel ball and passed through a 60-mesh sieve; (6) at 10T / cm 2 Under the pressing pressure of , the screened mixed magnetic powder is pressed into a ring of Φ15×Φ9.8×8.45mm through a mold; (7) The molded product is heated and cured at 180°C for 50 minutes; (8) The cured product is surface treated with electrophoretic epoxy resin (EP-703) at a film thickness of 0.020 mm; (9) Magnetizing the surface treated product to obtain the bonded magnet with low magnetic energy product and high coercive force.

[0038] Comparative Example 1 (directly mixing two magnetic powders and adding the glue): A method for preparing a bonded magnet with low magnetic energy product and high coercivity, comprising the following steps: (1) By weight, 2.5 parts of epoxy resin W-6C, 0.03 parts of curing agent dicyandiamide, and 0.03 parts of silane coupling agent KH550 were mixed uniformly to obtain magnetic powder adhesive; (2) adding magnetic powder glue into acetone, stirring and dissolving it evenly with a stirrer to obtain glue solution; (3) Weigh strontium ferrite magnetic powder (average particle size 500 mesh) and neodymium iron boron magnetic powder (grade 8-11, average particle size 200 mesh) and add them to a mixer, then add the glue solution and start stirring at a speed of 20 r / min; while stirring, heat the temperature in the container to 40°C and stir for 35 minutes; adjust the speed to 15 r / min and continue stirring, and evacuate to a vacuum degree of 0.09 Pa; stop evacuating, adjust the speed to 55 r / min, cool to 5°C with cooling water, and continue stirring for 10 minutes to obtain mixed magnetic powder; the strontium ferrite magnetic powder added is 5% of the mass of the neodymium iron boron magnetic powder, the mass of the magnetic powder glue in the glue solution is 2.0% of the total mass of the strontium ferrite magnetic powder and the neodymium iron boron magnetic powder, and the mass of the organic solvent is 8% of the total mass of the strontium ferrite magnetic powder and the neodymium iron boron magnetic powder; (4) The mixed magnetic powder is crushed by a Φ10×10 stainless steel ball and passed through a 60-mesh sieve; (5) at 10T / cm 2 Under the pressing pressure of , the screened mixed magnetic powder is pressed into a ring of Φ15×Φ9.8×8.45mm through a mold; (6) The molded product is heated and cured at 180°C for 50 minutes; (7) The cured product is surface treated with electrophoretic epoxy resin (EP-703) at a film thickness of 0.020 mm; (8) Magnetizing the surface treated product to obtain the bonded magnet with low magnetic energy product and high coercive force.

[0039] Comparative Example 2 (too much strontium ferrite powder): A method for preparing a bonded magnet with low magnetic energy product and high coercivity, comprising the following steps: (1) By weight, 2.5 parts of epoxy resin W-6C, 0.03 parts of curing agent dicyandiamide, and 0.03 parts of silane coupling agent KH550 were mixed uniformly to obtain magnetic powder adhesive; (2) adding magnetic powder glue into acetone, stirring and dissolving it evenly with a stirrer to obtain glue solution; (3) Weigh strontium ferrite magnetic powder (average particle size 500 mesh) and add it to the mixer, then add the glue solution and start stirring at a speed of 20 r / min; while stirring, heat the temperature in the container to 40°C and stir for 15 minutes; (4) Add NdFeB magnetic powder (grade 8-11, average particle size 200 mesh) into the mixer and continue stirring at a speed of 20 r / min for 20 min; adjust the speed to 15 r / min and continue stirring, and evacuate to a vacuum degree of 0.09 Pa; stop evacuating, adjust the speed to 55 r / min, cool to 5°C with cooling water, and continue stirring for 10 min to obtain mixed magnetic powder; the added strontium ferrite magnetic powder is 80% of the mass of the NdFeB magnetic powder, the mass of the magnetic powder glue in the glue solution is 2.0% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder, and the mass of the organic solvent is 8% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder; (5) The mixed magnetic powder is crushed by a Φ10×10 stainless steel ball and passed through a 60-mesh sieve; (6) at 10T / cm 2 Under the pressing pressure of , the screened mixed magnetic powder is pressed into a ring of Φ15×Φ9.8×8.45mm through a mold; (7) The molded product is heated and cured at 180°C for 50 minutes; (8) The cured product is surface treated with electrophoretic epoxy resin (EP-703) at a film thickness of 0.020 mm; (9) Magnetizing the surface treated product to obtain the bonded magnet with low magnetic energy product and high coercive force.

[0040] Comparative Example 3 (stirring speed is too fast): A method for preparing a bonded magnet with low magnetic energy product and high coercivity, comprising the following steps: (1) By weight, 2.5 parts of epoxy resin W-6C, 0.03 parts of curing agent dicyandiamide, and 0.03 parts of silane coupling agent KH550 were mixed uniformly to obtain magnetic powder adhesive; (2) adding magnetic powder glue into acetone, stirring and dissolving it evenly with a stirrer to obtain glue solution; (3) Weigh strontium ferrite magnetic powder (average particle size 500 mesh) and add it to the mixer, then add the glue solution and start stirring at a speed of 40 r / min; while stirring, heat the temperature in the container to 40°C and stir for 15 minutes; (4) Add NdFeB magnetic powder (grade 8-11, average particle size 200 mesh) into the mixer and continue stirring at a speed of 40 r / min for 20 min; adjust the speed to 30 r / min and continue stirring, and evacuate to a vacuum degree of 0.09 Pa; stop evacuating, adjust the speed to 55 r / min, cool to 5°C with cooling water, and continue stirring for 10 min to obtain mixed magnetic powder; the strontium ferrite magnetic powder added is 5% of the mass of the NdFeB magnetic powder, the mass of the magnetic powder glue in the glue solution is 2.0% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder, and the mass of the organic solvent is 8% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder; (5) The mixed magnetic powder is crushed by a Φ10×10 stainless steel ball and passed through a 60-mesh sieve; (6) at 10T / cm 2 Under the pressing pressure of , the screened mixed magnetic powder is pressed into a ring of Φ15×Φ9.8×8.45mm through a mold; (7) The molded product is heated and cured at 180°C for 50 minutes; (8) The cured product is surface treated with electrophoretic epoxy resin (EP-703) at a film thickness of 0.020 mm; (9) Magnetizing the surface treated product to obtain the bonded magnet with low magnetic energy product and high coercive force.

[0041] Comparative Example 4 (stirring speed is too slow): A method for preparing a bonded magnet with low magnetic energy product and high coercivity, comprising the following steps: (1) By weight, 2.5 parts of epoxy resin W-6C, 0.03 parts of curing agent dicyandiamide, and 0.03 parts of silane coupling agent KH550 were mixed uniformly to obtain magnetic powder adhesive; (2) adding magnetic powder glue into acetone, stirring and dissolving it evenly with a stirrer to obtain glue solution; (3) Weigh strontium ferrite magnetic powder (average particle size 500 mesh) and add it to the mixer, then add the glue solution and start stirring at a speed of 10 r / min; while stirring, heat the temperature in the container to 40°C and stir for 15 minutes; (4) NdFeB magnetic powder (grade 8-11, average particle size 200 mesh) is added to the mixer, and stirring is continued at a speed of 10 r / min for 20 min; then vacuum is evacuated to a vacuum degree of 0.09 Pa; vacuum evacuation is stopped, the speed is adjusted to 55 r / min, cooling to 5° C. with cooling water, and stirring is continued for 10 min to obtain mixed magnetic powder; the strontium ferrite magnetic powder added is 5% of the mass of the NdFeB magnetic powder, the mass of the magnetic powder glue in the glue solution is 2.0% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder, and the mass of the organic solvent is 8% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder; (5) The mixed magnetic powder is crushed by a Φ10×10 stainless steel ball and passed through a 60-mesh sieve; (6) at 10T / cm 2 Under the pressing pressure of , the screened mixed magnetic powder is pressed into a ring of Φ15×Φ9.8×8.45mm through a mold; (7) The molded product is heated and cured at 180°C for 50 minutes; (8) The cured product is surface treated with electrophoretic epoxy resin (EP-703) at a film thickness of 0.020 mm; (9) Magnetizing the surface treated product to obtain the bonded magnet with low magnetic energy product and high coercive force.

[0042] Comparative Example 5 (the organic solvent was not fully volatilized): A method for preparing a bonded magnet with low magnetic energy product and high coercivity, comprising the following steps: (1) By weight, 2.5 parts of epoxy resin W-6C, 0.03 parts of curing agent dicyandiamide, and 0.03 parts of silane coupling agent KH550 were mixed uniformly to obtain magnetic powder adhesive; (2) adding magnetic powder glue into acetone, stirring and dissolving it evenly with a stirrer to obtain glue solution; (3) Weigh strontium ferrite magnetic powder (average particle size 500 mesh) and add it into a mixer, then add the glue solution and start stirring at a speed of 20 r / min for 15 min; (4) Add NdFeB magnetic powder (grade 8-11, average particle size 200 mesh) into the mixer, and continue stirring at a speed of 20 r / min for 20 min; adjust the speed to 15 r / min and continue stirring, and evacuate to a vacuum degree of 0.09 Pa; stop evacuating, adjust the speed to 55 r / min, cool to 5°C with cooling water, and continue stirring for 10 min to obtain mixed magnetic powder; the added strontium ferrite magnetic powder is 5% of the mass of the NdFeB magnetic powder, the mass of the magnetic powder glue in the glue solution is 2.0% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder, and the mass of the organic solvent is 8% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder; (5) The mixed magnetic powder is crushed by a Φ10×10 stainless steel ball and passed through a 60-mesh sieve; (6) at 10T / cm 2 Under the pressing pressure of , the screened mixed magnetic powder is pressed into a ring of Φ15×Φ9.8×8.45mm through a mold; (7) The molded product is heated and cured at 180°C for 50 minutes; (8) The cured product is surface treated with electrophoretic epoxy resin (EP-703) at a film thickness of 0.020 mm; (9) Magnetizing the surface treated product to obtain the bonded magnet with low magnetic energy product and high coercive force.

[0043] Comparative Example 6 (excessive evaporation of organic solvent): A method for preparing a bonded magnet with low magnetic energy product and high coercivity, comprising the following steps: (1) By weight, 2.5 parts of epoxy resin W-6C, 0.03 parts of curing agent dicyandiamide, and 0.03 parts of silane coupling agent KH550 were mixed uniformly to obtain magnetic powder adhesive; (2) adding magnetic powder glue into acetone, stirring and dissolving it evenly with a stirrer to obtain glue solution; (3) Weigh strontium ferrite magnetic powder (average particle size 500 mesh) and add it to the mixer, then add the glue solution and start stirring at a speed of 20 r / min; while stirring, heat the temperature in the container to 60°C and stir for 15 minutes; (4) Add NdFeB magnetic powder (grade 8-11, average particle size 200 mesh) into the mixer, and continue stirring at a speed of 20 r / min for 20 min; adjust the speed to 15 r / min and continue stirring, and evacuate to a vacuum degree of 0.09 Pa; stop evacuating, adjust the speed to 55 r / min, cool to 5°C with cooling water, and continue stirring for 10 min to obtain mixed magnetic powder; the added strontium ferrite magnetic powder is 5% of the mass of the NdFeB magnetic powder, the mass of the magnetic powder glue in the glue solution is 2.0% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder, and the mass of the organic solvent is 8% of the total mass of the strontium ferrite magnetic powder and the NdFeB magnetic powder; (5) The mixed magnetic powder is crushed by a Φ10×10 stainless steel ball and passed through a 60-mesh sieve; (6) at 10T / cm 2 Under the pressing pressure of , the screened mixed magnetic powder is pressed into a ring of Φ15×Φ9.8×8.45mm through a mold; (7) The molded product is heated and cured at 180°C for 50 minutes; (8) The cured product is surface treated with electrophoretic epoxy resin (EP-703) at a film thickness of 0.020 mm; (9) Magnetizing the surface treated product to obtain the bonded magnet with low magnetic energy product and high coercive force.

[0044] The properties of the bonded magnets prepared in the above embodiments and comparative examples were tested, and the results are shown in Table 1; the magnetic properties were tested using a magnetometer, and the salt spray test used a 5 (wt)% NaCl solution.

[0045] Table 1: Bonded magnet performance test results.

[0046] As can be seen from Table 1, in Examples 1 to 8, the method of the present invention is used to mix strontium ferrite magnetic powder and neodymium iron boron magnetic powder, and the two can be evenly mixed, so that the magnetic properties of the obtained bonded magnet have a small fluctuation range, the fluctuation range of the maximum magnetic energy product is within 2%, the fluctuation range of the intrinsic coercive force is within 1%, and the film thickness of the epoxy resin layer on the surface is uniform, and the product has good corrosion resistance. At the same time, the obtained bonded magnet has a high coercive force and can achieve a continuous adjustable magnetic energy product of 3.0-8.0MGOe, which can meet the requirements of magnetic properties in different fields and improve the product cost performance.

[0047] In Comparative Example 1, strontium ferrite magnetic powder and neodymium iron boron magnetic powder are directly mixed and then the glue is added. Due to the difference in performance between the two, they cannot be mixed evenly, and the fluctuation range of the magnetic properties of the obtained bonded magnet is significantly improved compared with that in Example 1; the film thickness of the epoxy resin layer on the surface of the product cannot be kept consistent, resulting in a decrease in its corrosion resistance.

[0048] In Comparative Example 2, the added proportion of strontium ferrite magnetic powder is too high, and it cannot evenly adhere to the surface of the neodymium iron boron magnetic powder, resulting in reduced mixing uniformity, resulting in a larger fluctuation range of magnetic properties compared with Example 1.

[0049] In Comparative Example 3, the stirring speed during mixing is too fast, which easily causes local magnetic powder agglomeration, and the mixing of strontium ferrite magnetic powder, magnetic powder glue and neodymium iron boron magnet is uneven; in Comparative Example 4, the stirring speed during mixing is too slow, the magnetic powder cannot flow effectively, and the strontium ferrite magnetic powder cannot be mixed evenly with the magnetic powder glue and neodymium iron boron magnet, both of which will lead to an increase in the fluctuation range of the magnetic properties of the product.

[0050] In Comparative Example 5, the organic solvent is not fully volatilized after the strontium ferrite magnetic powder is mixed with the glue liquid, and the magnetic powder glue is too wet and cannot be adsorbed on the surface of the magnetic powder to solidify, resulting in the strontium ferrite magnetic powder being unable to effectively adhere to the surface of the neodymium iron boron magnet, and the two cannot be mixed evenly; in Comparative Example 6, the organic solvent evaporates too much, the magnetic powder glue has been fully solidified on the surface of the magnetic powder, and can no longer adhere to the neodymium iron boron magnetic powder, which is not conducive to the uniform mixing of the two; similarly, both will cause the magnetic properties of the product to fluctuate greatly.

Claims

1. A method for preparing a bonded magnet with low magnetic energy product and high coercivity, characterized in that the steps include: (1) dissolving magnetic powder glue in an organic solvent to obtain glue solution; (2) Add the glue solution to the strontium ferrite magnetic powder and stir at 15-30 r / min for 10-20 min at 40±5°C; (3) Add NdFeB magnetic powder, stir for 15-25 minutes under the same conditions, adjust the speed to 10-20 r / min, and evacuate to a vacuum degree of 0.08-0.1 Pa; stop evacuating, adjust the speed to 50-60 r / min, cool to 5±5°C, continue stirring for 5-15 minutes to obtain mixed magnetic powder; the strontium ferrite magnetic powder added is 0-70% of the mass of the NdFeB magnetic powder; (4) crushing and screening the mixed magnetic powder and then performing compression molding; (5) The molded product is heated and cured, epoxy resin surface treated and magnetized in sequence.

2. The method for preparing a bonded magnet with low magnetic energy product and high coercivity according to claim 1, characterized in that: The average particle size of the strontium ferrite magnetic powder is 400-600 meshes, and the average particle size of the neodymium iron boron magnetic powder is 100-250 meshes.

3. The method for preparing a bonded magnet with low magnetic energy product and high coercivity according to claim 1, characterized in that: In parts by weight, the components of the magnetic powder adhesive in step (1) include: 2-3 parts of epoxy resin, 0.35-0.55 parts of curing agent, and 0.02-0.04 parts of coupling agent.

4. The method for preparing a bonded magnet with low magnetic energy product and high coercivity according to claim 3, characterized in that: The curing agent is dicyandiamide and the coupling agent is KH550.

5. The method for preparing a bonded magnet with low magnetic energy product and high coercivity according to claim 1, 2 or 3, characterized in that: The mass of the magnetic powder glue added to the glue solution is 1.5-3.0% of the total mass of the strontium ferrite magnetic powder and the neodymium iron boron magnetic powder, and the mass of the organic solvent is 5-10% of the total mass of the strontium ferrite magnetic powder and the neodymium iron boron magnetic powder.

6. The method for preparing a bonded magnet with low magnetic energy product and high coercivity according to claim 1, characterized in that: In step (4), the mixed magnetic powder is vibrated and crushed by a Φ10×10 stainless steel ball and sieved through a 40-80 mesh sieve.

7. The method for preparing a bonded magnet with low magnetic energy product and high coercivity according to claim 1 or 6, characterized in that: The pressure during the compression molding in step (4) is 8-10T / cm 2 .

8. The method for preparing a bonded magnet with low magnetic energy product and high coercivity according to claim 1, characterized in that: The temperature during heating and curing in step (5) is 180±10°C, and the curing time is 50±10min.

9. The method for preparing a bonded magnet with low magnetic energy product and high coercivity according to claim 1 or 8, characterized in that: The thickness of the surface epoxy resin layer in step (5) is 0.015-0.025 mm.

Citation Information

Patent Citations

  • Composite bonded magnet and preparation method thereof

    CN117373768A

  • Bonded neodymium iron boron-ferrite permanent magnet and preparation method and application thereof

    CN117831926A

  • Mixing method for compression molding bonded magnetic powder and application of mixing method in bonded magnet

    CN118073040A

  • Rare earth hybrid magnet composition and magnet using the same

    JP2002110410A

  • Composition for resin-coupled magnet, method of manufacturing the same, resin-coupled magnet utilizing the same composition

    JP2004095791A